Educaçâo especial no município de Quaraí, RS: a realidade de duas escolas diante da Pandemia da Covid-19 - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This study aims to discuss the current school scenario in times of COVID 19 pandemic, particularly with regard to the school inclusion of students with disabilities in the context of remote classes, in the municipality of Quaraí/RS. As a methodology, a questionnaire was applied to two education teachers of the municipality mentioned, one being a regular school and the other a secondary school. exclusive service to students with special educational needs, in order to understand the challenges and possibilities within the context of remote teaching. The study is based on the theoretical assumptions of Menezes (2001); Camargo (2017); Moreira and Silva (2002) among others, also bringing the documents National Curricular Parameters and the Common National Curricular Base related to Special Education in the context of School Inclusion. Posteriorly, conceptualize that the content of the PCN brings greater contributions to the teacher than the BNCC, which apart from not dealing with inclusive special education directly, attributes for each school curriculum, which does not guarantee that it will be observed with the due attention and importance. Debate is essential as the BNCC has a normative character and has the prospect of guaranteeing education equal to all. Some of the results of this study show the difficulties and challenges faced by teachers to enable teaching and learning meaningful for your students, even when teaching remotely.
Keywords: Pandemia; Inclusão escolar; Ensino remoto; Pandemic; School inclusion; Remote learning; CNPQ::LINGUISTICA, LETRAS E ARTES